PENGARUH TINGKAT PENDIDIKAN ORANG TUA TERHADAP PERILAKU SOSIAL ANAK TK RAUDHATUL JANNAH - Putri Clawson; Anita Febriani (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2017)
In this study the method used is correlation, which is a method to provide a clear and accurate picture of the problem being examined. This research is not directed at testing hypotheses, but directed at describing variables or conditions as they are in a situation. this is in accordance with the opinion of Arikunto (2002: 131). The results of parental responses to the social behavior of children in kindergarten Raudhatul Jannah, in terms of overall indicators of parental responses to social behavior of children classified as "Agree" with a percentage of 65.00%. While the level of education of parents of children who have elementary education as many as 17 people with a percentage level of 56.67%, 9 percent of junior high school education with a percentage of 30.00%, and high school education of 4 people with a percentage of 13.33%, while parents with College education level does not exist. The results of the above calculations it is known that the value of the Produc Moment correlation between the level of parental education on social behavior of children is 0.511. If this price is consulted with the table r Product Moment obtained r table = 0.361 (for n = 30), then r count> r table or, 0.511> 0.361 in the "medium" category. This means that the level of parental education has a significant effect on social behavior of children in Raudhatul Jannah Kindergarten.